FAKTOR PENYEBAB PENYAKIT GINJAL KRONIK PADA PASIEN YANG MENJALANI TERAPI HEMODIALISIS DI UNIT HEMODIALISIS RUMAH SAKIT KHUSUS GINJAL RASYIDA MEDAN TAHUN 2019 - KASIH SANTIKA; SHAHRUL RAHMAN (JURNAL ILMIAH SIMANTEK, 2021)
Chronic kidney disease (CKD) is a pathological process with diverse etiologies, resulting in a progressive and irreversibledecline in kidney function. The prevalence of CKD in the last ten years has increased. Factors causing CKD vary greatlyfrom country to country. Hemodialysis is still the main kidney replacement therapy besides peritoneal hemodialysis andkidney transplantation. This study aims to determine the factors causing chronic kidney disease in patients undergoinghemodialysis therapy at the Medan Rasyida Kidney Special Hospital in 2019. A descriptive study with a total sampling of 307CKD patients undergoing hemodialysis. The data came from the patient's medical record which included the patient'sprevious medical history. The most common factors causing chronic kidney disease in hemodialysis patients werehypertension (59.6%), diabetes mellitus (32.2%), obstructive nephropathy (2.6%), gout nephropathy (2.3%), polycystickidney (2.0%) and glomerulonephritis (1.3%). Hypertension is the most common cause of CKD in Medan Rasyida KidneyHospital in 2019.